2006
DOI: 10.1097/01.wnr.0000224770.74528.d6
|View full text |Cite
|
Sign up to set email alerts
|

Understanding of physiological neural firing patterns through dynamical bifurcation machineries

Abstract: The characteristics of baroreceptor firing patterns were recognized in experiment, and their dynamics revealed in theoretical analysis. During blood pressure elevation, baroreceptors gradually exhibited bursting, continuous firing, and paradoxical bursting patterns. The bursting was generated through the repeated bifurcations between rest and spiking, the continuous firing was maintained without bifurcation, and the paradoxical bursting was generated through the bifurcations between spiking and a depolarizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 16 publications
0
21
0
Order By: Relevance
“…The dynamics of neural firing patterns and the bifurcations of firing patterns were of fundamental importance to the elucidation of neural coding mechanism (Braun et al 1994;Yang et al 2006). Various firing patterns, such as periodic firing, chaotic firing and stochastic resonance induced stochastic firing, were inspected in different nervous system (Chay 1985;Braun et al 1994;Ren et al 1997;Gu et al 2001Gu et al , 2003Gu et al , 2011aJia et al 2011;Du et al 2010;Guo 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The dynamics of neural firing patterns and the bifurcations of firing patterns were of fundamental importance to the elucidation of neural coding mechanism (Braun et al 1994;Yang et al 2006). Various firing patterns, such as periodic firing, chaotic firing and stochastic resonance induced stochastic firing, were inspected in different nervous system (Chay 1985;Braun et al 1994;Ren et al 1997;Gu et al 2001Gu et al , 2003Gu et al , 2011aJia et al 2011;Du et al 2010;Guo 2011).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] Dynamics underpinning various neuronal firing patterns have been eventually revealed by theoretical analysis in neuronal models, while mechanisms underlying the transitions between different firing patterns are being elucidated by means of bifurcation theory. [1][2][3][4]8 For example, neural excitable membranes have been demonstrated to transit from resting state to tonic firing through Hopf bifurcation and saddle-node bifurcation, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] The bifurcation procedures of neural firing activities exhibit the way in which a neuron changes its firing rhythms in response to regulatory parameter changes, and thus are essential for understanding the mechanisms of neural coding. 9 In studies of nonlinear dynamics of neuronal firing activities, the transition from resting state to tonic firing is an important issue, because during this transition most neurons generate their significant output signals. In transition from resting to firing, noise has been found to play critical roles and may generate stochastic firing patterns by its interplay with the dynamics of the neuronal systems.…”
Section: Introductionmentioning
confidence: 99%
“…It was also reported that, even if blood pressure is in the physiological range, some baroreceptors generate a temporal pattern in which they stop firing (i.e., rest) in the systolic phase but resume firing in the diastolic phase [14,15]. The results indicate that at least some baroreceptors can stop firing as blood pressure increases in the systolic phase.…”
mentioning
confidence: 96%